Sigil application based e-module validity in statistics material for middle school students - R. Rahmida; Zulfitri Aima; Audra Pramitha Muslim (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to evaluate the validity of the Sigil application-based E-Module on statistics material so that it can be used as a source of learning mathematics, especially on statistics material. This type of research is classified as development research (Research & Development/R&D) with the development model proposed by Plomp. However, this research is limited to the validity stage of the E-Module only. The e-module was validated by 3 experts consisting of 2 material experts and 1 media expert. The instrument used in this research is a validity questionnaire. Data validity was tested using a Likert scale. The results of the study show that the results of the validity of the Android-based E-Module using Sigil are 89,83%.